Her : a novel - Lane, Harriet, 1969- (New York : Little, Brown and Company, 2015)
"On the face of it, Emma and Nina have very little in common. Isolated and exhausted by early motherhood, Emma finds her confidence is fading fast. Nina--sophisticated, generous, effortlessly in control--seems to have all the answers. It's easy to see why Emma is drawn to Nina. But what does Nina see in her? A seemingly innocent friendship slowly develops into a dangerous game of cat and mouse as Nina eases her way into Emma's life. Soon, it becomes clear that Nina wants something from the unwitting Emma--something that might just destroy her"--
Kirkus Reviews
Library Journal
Publishers Weekly
Booklist
Keywords: Mothers -- Fiction; Female friendship -- Fiction; Domestic fiction; Suspense fiction